Inertial force balance and ADAMS simulation of the oscillating sieve and return pan of a rice combine harvester - Wei, Chuncai; Xu, Lizhang; Wang, Jianting; Li, Yaoming (International Journal of Agricultural and Biological Engineering, 2018)
To reduce the inertial force of the oscillating sieve and return pan of a rice combine harvester, partial equilibrium was adopted. Firstly, based on the kinematic analysis of a slider-crank mechanism, the appropriate mass of counterweight intervals was achieved. Then, an ADAMS dynamic simulation was used to determine the optimum balance mass of the oscillating sieve and return pan individually. Considering the relative motion between the return pan and the oscillating sieve, the overall inertial force of the two parts would be reduced. The simulation results indicated that the optimum counterweight of the oscillating sieve was 15.5 kg based on an analysis of the movement tracks of the mass center and overall inertial force. The results also showed that the overall balance of inertial force not only reduced the counterweight but also decreased the overall inertial force of the oscillating sieve and return pan. Finally, a search for the most suitable crank initial angle of the return pan to reduce the overall inertial force and optimize the overall balance revealed three groups of initial angles: φ=0°, φ=45°, and φ=90°. The results indicated that arranging the initial angle of the crank of the oscillating sieve and return pan in the same position (φ=90°) was the most favorable for reducing the overall inertial force. In this situation, the optimum counterweight of the oscillating sieve was only 14.0 kg. The results can provid references for the design of the overall balance of the inertial force in the cleaning components of a combine harvester. Keywords: rice combine harvester, oscillating sieve, return pan, inertial force balance, ADAMS DOI: 10.25165/j.ijabe.20181101.2978 Citation: Wei C C, Xu L Z, Wang J T, Li Y M. Inertial force balance and ADAMS simulation of the oscillating sieve and return pan of a rice combine harvester. Int J Agric & Biol Eng, 2018; 11(1): 129–137.